Analisis Willingness To Pay Pengunjung Ekowisata Desa Budaya Kertalangu dalam Upaya Pemeliharaan Lingkungan - MAHITARANI, A.A. AYU ISA; BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Analysis of Willingness To Pay for Ecotourism Visitors in Kertalangu Cultural Village in Environmental Conservation Efforts Kertalangu Cultural Village is one of the tourist attractions in Denpasar that is oriented towards environmental conservation and cultural arts. This study aims to determine the socio-economic characteristics of visitors to the jogging track of Ecotourism Village at the Kertalangu Cultural Village and to estimate the value of willingness to pay (WTP) the entrance ticket to the jogging track of ecotourism area at the Kertalangu Cultural Village. Data on socio-economic characteristics of respondents were collected through the Survey Contingent Valuation Method (CVM) to 100 samples in the jogging track area of the Kertalangu Cultural Village Ecotourism using a closed-ended dischotomous choice questionnaire. The estimation of WTP used STATA 11.0 software. The WTP estimation results show that respondents are willing to pay for an entrance ticket to the jogging track Ecotourism area in the Kertalangu Cultural Village of Rp. 12,692.3. The socioeconomic variable that influences the decision of respondents to be willing to pay entrance fees for jogging track in the Kertalangu Cultural Village Ecotourism is the level of education. Based on the estimated results of willingness to pay for an entrance ticket for an Ecotourism jogging track area in Kertalangu Cultural Village, which is charged to visitors is Rp. 12,692.3 per person and this fund is used for the maintenance or conservation efforts of an Ecotourism jogging track area in Kertalangu Cultural Village. The average value of visitors' WTP can be used as a reference or consideration in determining the entrance ticket in the jogging track ecotourism area of Kertalangu Cultural Village. Limitations of this study, which is only carried out in Ecotourism in the Cultural Village of Kertalangu so that to be implemented at the level of Ecotourism in general, this research needs to be extended to Ecotourism areas that do not charge entrance ticket to visitors.